A Novel Bacteriophage Lysin-Human Defensin Fusion Protein Is Effective in Treatment of Clostridioides difficile Infection in Mice - Peng, Zhong; Wang, Shaohui; Gide, Mussie; Zhu, Duolong; Lamabadu Warnakulasuriya Patabendige, Hiran Malinda; Li, Chunhui; Cai, Jianfeng; Sun, Xingmin (Frontiers in Microbiology, 2019)
Clostridioides difficile is the leading cause of worldwide antibiotics-associated diarrhea. In this study, we report the construction and evaluation of a novel bacteriophage lysin-human defensin fusion protein targeting C. difficile. The fusion protein, designated LHD, is composed of two parts connected by a 3-repeating unit linker “(GGGGS)3”: the catalytic domain of a lysin protein from a C. difficile bacteriophage phiC2 (LCD) and the functional domain of a human defensin protein HD5. Lytic assays showed that LHD protein had a potent lytic activity against different types of clinical C. difficile strains, including the epidemic 027, 078, 012, and 087 strains. The minimum inhibitory concentration (MIC) of LHD was 0.78 μg/ml, which was lower than the MIC of the protein LCD (1.56 μg/ml), and the MICs of metronidazole (4 μg/ml) and vancomycin (4 μg/ml). In addition, the LHD protein could lyse C. different strains in different pHs (6.0, 7.0, and 8.0). Evaluation of LHD potency in vivo using mouse model of C. difficile infection (CDI) showed that administration of the LHD protein (twice daily for seven days) was effective in mitigating the symptoms and reducing the death from CDI. Treatment with LHD also significantly decreased the number of C. difficile spores and the toxin level in feces from the infected mice. Our data suggest that this novel lysin-human defensin fusion protein has a potential on CDI control.